Challenging the traceability of natural gold by combining geochemical methods: French Guiana example. (June 2021) - Pochon, Anthony; Desaulty, Anne-Marie; Bailly, Laurent; Lach, Philippe
Abstract: Considering the high economic importance and worldwide distribution of gold, the ability to identify its provenance is critical and challenging to ensuring a responsible supply chain from deposit to consumer, especially within conflict-affected areas. Here we present an innovative approach to trace the provenance of natural gold from French Guiana through a combination of geochemical and statistical methods. This approach is divided in three steps and allows the identification of illicit gold, the certification of the declared gold origin coming from legal operators and, in some cases, the identification of unknown gold. French Guiana was chosen as a demonstration case of our approach because it is a well-known conflict-affected area where illegal mining is widespread. In the first step, we showed that the use of illegal Hg amalgamation can be easily revealed by looking the gold grain morphology with an optical microscope or by detecting the Hg with laser-induced breakdown spectroscopy that allow direct detection on the field. In the second and principal step, we demonstrated that a declared provenance of gold can be certify with a high degree of confidence by measuring the Ag content of a gold grain population and by checking it against a database with the Kolmogorov-Smirnov statistic. In the final step that allows the identification of the origin of unknown gold, we used (i) the content of minor elements (Cu and Hg), (ii) the identification of mineral inclusions and their relative proportions within samples and (iii) the trace element composition of natural gold grains determined by LA-ICP-MS and coupled with a permutational multivariate analysis of variance and a similarity percentage analysis. This method allows the identification of the provenance of 69% of the gold samples; the provenance of other gold populations (31%) cannot be identified because of their geological similarity with other groups. The traceability of natural gold can be guaranteeing with our innovative approach, in particular by certifying declared gold population provenance. Further challenges to be addressed will be the implementation of such approach in others conflict-affected regions to support the global supply chain of gold. Highlights: The Ag content is an excellent proxy to certify the origin of natural gold Combination of various geochemical methods is needed to identify unknown gold origin. Laser-induced breakdown spectroscopy is powerful to identify gold extracted by Hg.